Fertility-associated biochemical components in seminal plasma and serum of buffalo (Bubalus bubalis) bulls - Almadaly, Essam A.; Abdel-Salam, Abdel-Basaer S.; Sahwan, Ferial M.; Kahilo, Khaled A.; Abouzed, Tarek K.; El-Domany, Wael B. (Frontiers in Veterinary Science, 2023)
The present study looks for components in seminal plasma (SP) and/or serum that are closely related to in vivo fertility of buffalo bulls. Fourteen healthy mature buffalo bulls were classified according to their in vivo fertility into fertile (n = 10) and subfertile (n = 4) groups. Semen and serum samples were collected from all animals for 12 replicates. The collected ejaculates were examined for sperm characteristics before being centrifuged to collect SP for hormonal (FSH, LH, testosterone, and IGF-1), biochemical [total antioxidant capacity (TAC), catalase (CAT), glutathione peroxidase (GPx), nitric oxide (NO), malondialdehyde (MDA), fructose, total protein, albumin, triglycerides, cholesterol, and high-density lipoprotein (HDL)] and proteomic (SDS-PAGE) analyses. Likewise, serum levels of FSH, LH, testosterone, IGF-1, glucose, total protein, albumin, triglycerides, cholesterol, and HDL were determined. All sperm characteristics and the majority of sperm kinematics were (P < 0.01) different between fertile and subfertile groups. Seminal and serum levels of FSH, LH, testosterone, and IGF-1 were higher (P < 0.01) in the fertile group, but only seminal fructose, total protein, albumin, triglycerides, cholesterol, and HDL were higher (P < 0.01) in the fertile group. Moreover, the fertile group had greater TAC, CAT, GPx, and NO, but the subfertile group had greater MDA. Protein bands of 14, 15, 26, 30, and 55 kDa were larger and denser in the SP of the fertile group but were smaller and faint to absent in that of the subfertile group. Also, the protein fractions of detected protein bands demonstrated a substantial influence of fertility on those of 16, 26, 30, and 55 kDa. In conclusion, sperm characteristics and kinematics with serum, and/or seminal hormonal and biochemical components, should be evaluated for reliable prediction of buffalo bull fertility. Furthermore, protein bands of 26, 30, and 55 kDa may represent fertility-associated proteins in buffalo bull SP.